PENGARUH PENDEKATAN STRATEGI RESOURCE BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI MADRASAH ALIYAH NEGERI 3 MEDAN - Muhammad Bagas F; Edi Suprayetno (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This study aims to analyze and know the Mathematics students’ learning outcome of grade XI of Madrasah Aliyah Negeri 3 Medan by applying resource based learning approach. This quasi-experimental study used a non-equivalent control group design with pre-test and post-test. . The sample of this study were 80 students who were divided into two classes, namely 40 students as the control class (class XI IPS) and 40 students as the experimental class (Class XI IPA1). The sampling technique used was purposive sampling. The results of this study indicated that by giving the pretest to the experimental and control classess, it was gained that the average value of the experimental class wa 33.125 and the average value of the control class wa 38.275. the experimental class is 81,425 and the control class is 43.9. From the results of this study, it can be concluded that there is was positive effect of the resource based learning approach on students' mathematics learning outcomes and it is recommended to develop resource based learning learning approach in learning process..